Hydrodynamic sequential injection system for a rapid dichlorophenol indophenol precipitation test for hemoglobin E - Supaporn Kradtap Hartwell (2018)
Dichlorophenol indophenol precipitation (DCIP) test is a screening method for unstable hemoglobins (Hb). An automatic system for a rapid DCIP test was developed based on stopped-flow hydrodynamic sequential injection. The system overcomes the problems of the conventional DCIP test such as long analysis time and imprecision, which are due to temperature fluctuation and imprecise detection timing. The flow based DCIP system can shorten the incubation time (usually 25 min to 1 h) to 3 min by using a higher temperature of 50°C instead of 37-40°C as in the conventional method. The reagents used were very simple and the whole process was done online with a microcontroller for controlling time. The clearness of the mixture was monitored with a spectrophotometer to improve precision as compared to the bare eyes observation method used in conventional DCIP test. The system could differentiate the HbE carriers (positive group) from negative group which agreed with the routine screening method using anion exchange micro-column. © 2009 Springer-Verlag.